Relationship between isokinetic strength of the knee joint and countermovement jump performance in elite boxers - Chao Chen; Zhalel Ali; Muhammad Abdul Rehman Rashid; Marchibayeva Ulbossyn Samethanovna; Guodong Wu; Sagidolla Mukhametkali; Tussipkan Dilnur (PeerJ, 2023)
Background The lower limbs play a key role to develop the linear momentum for hitting power in effective boxing. The knee extensor and flexor strength guarantees the dynamic stability of boxers. The insufficient extensor strength of the lower extremities causes compensation during flexion resulting in movement errors or damage to knee joint muscles. This study was conducted to explore the isokinetic concentric strength of the knee flexor and extensor and the relationship between isokinetic knee extensors strength and countermovement jump (CMJ) performance in elite boxers. Methods Thirteen elite male boxers (Age: 25.15 ± 3.98 years, height 1.72 ± 0.04 m, weight 61.82 ± 10.46 kg, training years = 11.56 ± 2.67 years) performed the CMJ, and the isokinetic knee test was performed using the Biodex dynamometer. Results The maximal isokinetic peak torque of the knee extensor and flexor muscles was recorded at three angular velocities (60°/s, 180°/s, and 240°/s) on both sides of the legs. The relative peak value of torque in the knee extensors decreased significantly with increasing angular velocity. A difference in relative peak torque (RPT) was only seen at 60°/s in knee flexors. However, the H/Q ratio increased as the velocity increased from 60°/s to 240°/s (P < 0.05). The highest peak torque was found in the knee extensors at a velocity of 240°/s (r = 0.73, P < 0.001). The correlation between RPT and vertical jump height was the strongest at 240°/s. The strongest relationship was found between the height of the CMJ and the RPT of the deficit of knee extensors. Conclusions We suggest that explosive force training of the isokinetic muscles should be optimally carried out at a speed of 240°/s. The results of this study provide a reference for boxers to improve their jump height and lower-limb explosive strength through isokinetic strength training of the knee flexor and extensor.